EPISTEMOLOGI DAN RUMPUN KEILMUAN KOMUNIKASI PENYIARAN ISLAM - Zamroni, Mohammad (Universitas Negeri Yogyakarta, 2015)
The existence of Islamic communication and broadcasting as a field of scientific disciplines still seems to be a question that has not got the answer. This question is often addressed on how the epistemology and the clumps of communication and broadcasting science. To that end, in-depth studies need to be done by tracingthe philosophy of science as basic science includes ontology, epistemology, and axiology.This study became urgent as well as to ward off dichotomy between general sciences and the religious sciences (Islam). One approach that can be used as a reference is an integrative interconnective science paradigm to integrate between Science and Islam. So the epistemology of communication science is the study of Communication sciencedisciplinethat studies broadcasting and journalism as well as others. While the Islamic Broadcasting Studies as a field of Dakwahstudy that is becoming core values with the Islamic perspective. It is being in tune with the vision of IslamicCommunication and Broadcasting majors that is leading in the assessment and development of communication science and Islamic broadcasting perspective.Eksistensi Komunikasi dan Penyiaran Islam sebagai bidang disiplin ilmu nampaknya masih menjadi pertanyaan yang belum mendapat jawaban.Pertanyaan ini sering ditujukan pada bagaimana epistemologi dan rumpun komunikasi dan ilmu penyiaran.Untuk itu, studi mendalam perlu dilakukan dengan menelusuri filsafat ilmu sebagai ilmu dasar meliputi ontologi, epistemologi, dan studi aksiologi.Penelusuran ini menjadi mendesak guna menangkal dikotomi antara ilmu-ilmu umum dan ilmu-ilmu agama (Islam).Salah satu pendekatan yang dapat digunakan sebagai referensi adalah paradigma ilmu integratif-interkonektif untuk mengintegrasikan ilmu dengan Islam.Epistemologi keilmuan jurusan Komunikasi dan Penyiaran Islam adalah pengkajian disiplin Ilmu Komunikasi dengan bidang kajiannya broadcasting dan jurnalistik serta lainnya. Sedangkan Penyiaran Islam sebagai bidang kajian Ilmu Dakwah yang menjadi core values dengan perspektif Islamnya. Hal ini menjadi selaras dengan visi jurusan Komunikasi dan Penyiaran Islam yaitu terdepan dalam pengkajian dan pengembangan ilmu-ilmu komunikasi dan penyiaran Islam yang berparadigma Islam.Keywords: Epistemology, Clumps Scientific, Communications and Broadcasting Islam.